(3GdBKGQ GdHGbjIs - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeJYGdi Yf GdGVOGO hGdGTHGg hHYO abO SCdfi GMO GdGOHGA Yf GdJhGQjN GdJi jSJYedgG GdGee s
(3BNQgG (B:s
(3OhdI ehdGfG GdGejQ GdSjO GdGLd GdefUhQ hdi GdfYe hdfNJe BNQ GdcJGH HGdMeO ddg GdPi fUQ hgOi s
(3HgG GdYOjO ef GdLOGhd hGdQehRs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B9s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs